SOME ISSUES OF ORGANIZING THE ACTIVITY OF ADMINISTRATIVE COURTS (World Bulletin of Social Sciences, 2023)
In this article, the reforms carried out in the last 5 years in order to properly organize the activities of the courts and ensure the quality and efficient implementation of the judicial activities are briefly discussed. Also, based on the specific features of the cases handled by the administrative courts, proposals were made on the effective organization of their activities